Critical reading of Gibran's world in The Prophet - Al-Khazraji, Nidaa Hussain Fahmi; Abdullah, Mardziah Hayati; Wong, Bee Eng (Canadian Center of Science and Education, 2013)
Gibran Khalil Gibran (1882-1931), the Lebanese writer, poet, artist and philosopher, was the bearer of faith in the unity of all religions. He was a key figure in the history of modern EnglishandArabic literature in early 20th Century.The present paper is to show how Gibran represents the world and undesirable social practices in the time of writing his greatest book The Prophet (1923). Gibran lets the readers fell that the prophet (Al-Mustafa) doesn’t belong to this very world; he comes to Orphalese to teach humanity and to correct the society under the tenets of all major religious. Each character in The Prophet, except Al-Mustafa, resamples one member of the deformed society who seeks deliverance. Gibran shortens the process of life and its needs in the 28 texts allowing the readers take an active role to interpret and to dictate the context on oblique hints and innuendo. Gibran views the world as a place that lacks love and peace, where individuals’ life is depraved and corrupted. The most obvious, Gibran is speaking through the mouth of Al-Mustafa preaching many commandments, disciplines and rituals.